Expression of LHCG receptors in the human penis. (2nd January 2020) - Zirnask, Helen; Pöllanen, Pasi; Suutre, Siim; Kuuslahti, Marianne; Kotsar, Andres; Pakarainen, Tomi; Kokk, Kersti
Abstract: The aim of this study is to investigate the expression of the luteinizing hormone/choriogonadotropin (LHCG) receptor in the human penis to see, if the luteinizing hormone (LH) effects are possible in the spongious and cavernous tissue of the penis. The number of men with erection disturbances increases significantly simultaneously with the elevated LH concentrations between 40 and 70 years. It is possible that the elevated LH concentrations may influence locally the erectile mechanisms. The precondition for this is the expression of LHCG receptors in the penis. Penile tissue was obtained from three patients undergoing total or partial penectomy due to a rectal cancer with secondary penile metastasis or squamous cell carcinoma of the penis. Immunohistochemistry was used for the detection of the LHCG receptor. Positive immunoreaction for LHCG receptors was discovered in the endothelial cells of cavernous spaces in the corpus cavernosum and corpus spongiosum penis, also in the endothelial cells of the capillary walls in all patients. Our results show that LHCG receptor is expressed in the spongious and cavernous tissue of the human penis. This finding suggests that LH can affect the spongious and cavernous tissue in human and play a significant role in the development of erectile dysfunction among the aging men.